Technical failure of endoscopic ultrasound-guided choledochoduodenostomy: multicenter study on rescue techniques, consequences, and risk factors - Beunon, Clara; Debourdeau, Antoine; Schaefer, Marion; Wallenhorst, Timothée; Perez-Cuadrado-Robles, Enrique; Belle, Arthur; Gonzalez, Jean-Michel; Camus Duboc, Marine; Caillol, Fabrice; Toudic, Hervé-Pierre; Pioche, Mathieu; Danset, Jean Baptiste; Sportes, Adrien; Brieau, Bertrand; Ben Soussan, Emmanuel; Petiet, Mathilde; Martin, Antoine; Oumrani, Sarra; Maire, Frédérique; Lemmers, Arnaud; Prat, Frédéric; Caillo, Ludovic; Gérard, Romain; Albouys, Jérémie; Lorenzo, Diane; and the ETC Working Group; Ouazzani, Sohaib; Barret, Maximilien; Quénéhervé, Lucille; Pauphilet, Cyrille; Jacques, Jérémie; Vanbiervliet, Geoffroy (Endoscopy, 2025)
Background We aimed to determine risk factors for technical failure of endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS), evaluate short- and long-term consequences, and identify salvage techniques in patients with biliary obstruction.Methods This retrospective multicenter study of EUS-CDS (2018–2024) included technical failure, classified as type 1 (digestive flange mispositioned), type 2 (biliary flange mispositioned), type 3 (stent deployment failure), type 4 (catheter/lumen-apposing metal stent [LAMS] through the bile duct), and type 5 (others). Controls were successful EUS-CDS in the same center and period. The primary end point was risk factors for failure. Secondary end points were endoscopic rescue techniques and immediate- and long-term consequences.Results Technical failure occurred in 7 % (95 %CI 5–9). Across 23 centers, 296 patients were analyzed (mean age 71 [SD 16] years, 53 % male), including 100 technical failures: type 1 (26 %), type 2 (41 %), type 3 (11 %), type 4 (6 %), type 5 (16 %). Risk factors for technical failure in multivariate analysis included CBD diameter ≤ 15 mm, duodenal stenosis, wired technique, and low operator experience (≤ 10 LAMS). Endoscopic salvage was successful in 77 %, with 53 % using a covered metal stent and 22 % using a new LAMS. Early failures were mild in 56 % of cases, but 12 % resulted in death within 30 days. Immediate endoscopic salvage reduced severe clinical adverse events (P < 0.001) and increased success rates (P < 0.001).Conclusions EUS-CDS failures were not rare and were severe in half of cases. Recognizing risk factors, identifying failures during the procedure, and knowing endoscopic salvage methods are crucial.